RIETVELD STRUCTURE REFINEMENT OF NH4-EXCHANGED NATURAL CHABAZITE - Gualtieri A.F.; Passaglia E. (My University, 2006)
In this work the results of the X-ray Rietveld structure refinement of a natural and the corresponding NH4-exchanged chabazite from Nova Scotia (Canada) are exposed. Experimental data were collected using a laboratory powder diffractometer equipped with copper tube and graphite crystal monochromator. The outcome of this crystal-structure study is useful for (i) understanding the structure modifications induced by the NH4+ exchange; (ii) understanding the physical-chemical and technological properties of NH4-chabazite, a zeolite vastly used for industrial applications; (iii) understanding the mechanism of proton conductivity of the NH4-exchanged zeolites, precursors of catalytically active H+ forms. The position and orientation of the NH4+ ion were initially refined using the rigid body model and later with the aid of soft constraints. The coordination number of the ammonium ion is 9 with two equally possible and mutually exclusive configurations. One coordination environment includes 3 oxygen atoms O3, 3 oxygen atoms O4, and 3 H2O molecules W2a. The other environment includes 3 oxygen atoms O3, 3 oxygen atoms O4, and 3 H2O molecules W3. As already shown for other NH4-zeolites, the N-O distances are larger than the N-H2O distances. The local geometry of the ammonium ion points to a monodentate configuration. A bidentate configuration of the hydrogen bonds for NH4+ is also possible if the long H2...O3 separation is considered to be at bond distance. For industrial and technological applications, knowledge of the local environment of NH4+ in the cavities of zeolites is important. Weak hydrogen bonds with framework oxygen atoms implies that the ammonium molecule can be easily exchanged or desorbed. This property is attractive for agronomy, horticulture and soil remediation where zeolite can be added to chemical fertilizers to improve the soil's chemical and physical properties for plant growth, to increase fertilizer efficiency and to reduce the leaching of nutrients, to reduce the dissolution rate of a soluble fertilizer via ion exchange or combination of mineral dissolution and ion exchange, and to act as remediation agents in soils. © 2006 E. Schweizerbart'sche Verlagsbuchhandlung.
Keywords: AMMONIUM ION; CHABAZITE; CHEMICAL ENVIRONMENT; INDUSTRIAL APPLICATIONS; RIETVELD REFINEMENT